2017
DOI: 10.1093/femsle/fnx087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl-L-cysteine on the membrane vesicle release and growth of respiratory pathogens

Abstract: Bacterial infections contribute to the disease progression of chronic obstructive pulmonary disease by stimulating mucus production in the airways. This increased mucus production and other symptoms are often alleviated when patients are treated with mucolytics such as N-acetyl-L-cysteine (NAC). Moreover, NAC has been suggested to inhibit bacterial growth. Bacteria can release membrane vesicles (MVs) in response to stress, and recent studies report a role for these proinflammatory MVs in the pathogenesis of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…7), consistent with a report that NAC inhibited the production of extracellular polysaccharide and reduced bacterial adhesion. 45 The study of Volgers et al 46 also demonstrated that NAC repressed membrane vesicle formation and attenuated pathogenic capacity. In addition, the present study showed that NAC treatment interfered with metabolism-related biosynthesis and the redox system of intestinal bacteria in HFD-fed mice (Fig.…”
Section: Figurementioning
confidence: 97%
“…7), consistent with a report that NAC inhibited the production of extracellular polysaccharide and reduced bacterial adhesion. 45 The study of Volgers et al 46 also demonstrated that NAC repressed membrane vesicle formation and attenuated pathogenic capacity. In addition, the present study showed that NAC treatment interfered with metabolism-related biosynthesis and the redox system of intestinal bacteria in HFD-fed mice (Fig.…”
Section: Figurementioning
confidence: 97%
“…As thiol modifications appear to modulate the formation and functions of EVs upon cell exposure to pro-oxidant conditions, thiol protection may be a promising strategy to prevent detrimental changes in EV signaling under such conditions. Indeed, several thiol-bearing small molecules, such as NAC; NACA and glutathione are able to prevent EV induction by a variety of ROS, RCS and pro-inflammatory stimuli, likely by scavenging thiol-reactive compounds and preventing them from reacting with cellular thiols [ 41 43 , 52 , 53 , 98 100 ]. NAC also inhibits EV-associated release of TF and PS by cells exposed to oxidant conditions and consequently decreases the procoagulant potential of EVs [ 42 , 52 , 53 ].…”
Section: Thiol Protection To Prevent Ev Modifications: Therapeutic Immentioning
confidence: 99%
“…The researchers revealed that the mean patient-rated severity score associated with sputum production was decreased in the NAC group between visits 1 and 4 (P=0.08) in comparison to the controls, and none of the patients had to use any additional expectorant agents after receiving nebulization. Similarly, Volgers et al [74] studied high dose nebulized NAC in COPD patients and demonstrated that NAC exerts a strong bacteriostatic effect in patients with airway conditions.…”
Section: Introductionmentioning
confidence: 98%